Private Autonomy, Principle of Legality, and Civil Law - Palacios Martínez, Eric (2007)
This article examines the relationship between private autonomy and the law in the field of civil law. The author believes that, although modern developments or current phenomena, such as globalisation and the weakening of the public sphere, are intended to strengthen civil law, they are in fact undermining its foundations. To that extent, these changes are distorting the conception of private autonomy and the legal system, which poses a problem for civil law and law in general. Furthermore, the author argues that private autonomy, although a social phenomenon that precedes the state system, cannot be equated with the functions and powers of the state. In that context, this paper provides a thoughtful critique of the current challenges facing civil law in relation to private autonomy and the principle of legality.